Evaluation of postural control among diabetes mellitus patient using gans sop test - Ab Shukor, Nor Farawaheeda (2017)
Balance is the ability to maintain the body’s center of mass over its base of support. Normal body’s balance system essential for us to have normal vision while we are moving, orientation with respect to gravity, and postural adjustment to maintain posture and stability in various conditions. As we know, Diabetes Mellitus can cause many effect to our body system include balance problem. Gait characteristics and balance are altered in diabetic patients. The Gans SOP Test using Bal ex Foam is used to evaluate balance performance. It is combination of the Romberg, Modified Romberg, standing on the form and Stepping Fukuda Tests.The aim to evaluate the postural changes of patient with Diabetic Mellitus using Gans SOP Test. A total of 59 subjects with age range 20 to 60 were recruited for this study and were divided into two group of normal and group of Diabetes Mellitus patient. Subjects were tested with Gans SOP test which consist of seven conditions. The degree of sway and turning was recorded for each condition tested. Statistical analysis using Mann Whitney test showed significant difference with p<0.05 were found in three out of seven condition tested. However the result have correlation with the age factor which show that age are one of the contribution factor that cause the results to be significant. The other 4 condition showed no significant difference. In conclusion, the finding of Gans SOP test are found that Diabetes Mellitus patient showed more sway compare to the normal group. However, in this test, the contribution of age also maybe one of the factor that cause the Diabetes Mellitus group have significant sway compare to the normal group. Overall, the patient with Diabetes Mellitus still have more degree of swaying compare to the normal group regardless with eyes open or closed.